2013
DOI: 10.1099/ijs.0.045997-0
|View full text |Cite
|
Sign up to set email alerts
|

Celerinatantimonas yamalensis sp. nov., a cold-adapted diazotrophic bacterium from a cold permafrost brine

Abstract: A facultatively anaerobic nitrogen-fixing bacterium, strain C7 T , was isolated from a permafrost cryopeg on the Yamal Peninsula, Russia. Comparative analysis of 16S rRNA gene sequences revealed that this bacterium was closely related to Celerinatantimonas diazotrophica S-G2-2 T with a similarity of 95.5 %. Strain C7T differed from Celerinatantimonas diazotrophica in its ability to hydrolyse gelatin and inability to use D-mannose, melibiose, L-rhamnose, myo-inositol, lactose, lactulose, D-mannitol, trehalose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recently, Chua et al [58] defined the Antarctic briny environments as liquid oases for microbial life. Hypersaline brine lenses are unique aquatic systems that are thought not to undergo changes via external influence over geological timescales [59]. In this regard, the brine TF4 had probably experienced a chemico-physical exchange with the atmosphere, whereas TF5 was supposed to be isolated since 12000 cal years BP [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chua et al [58] defined the Antarctic briny environments as liquid oases for microbial life. Hypersaline brine lenses are unique aquatic systems that are thought not to undergo changes via external influence over geological timescales [59]. In this regard, the brine TF4 had probably experienced a chemico-physical exchange with the atmosphere, whereas TF5 was supposed to be isolated since 12000 cal years BP [23].…”
Section: Discussionmentioning
confidence: 99%
“…Permafrost, including cryopegs, is a repository of diverse viable microorganisms represented by Gram-positive and Gram-negative, aerobic, anaerobic, spore-forming and asporogenous bacteria. [69][70][71][72][73][74][75][76] In numerous permafrost deposits, primarily of lacustrine and marine origin, viable methane-producing archaea have been found. [77][78][79][80] Permafrost has been shown to contain other groups of microorganisms, for example yeasts, 81,82 and mycelial fungi.…”
Section: Diversity Of Organisms In Permafrostmentioning
confidence: 99%
“…Permafrost, including cryopegs, is a repository of diverse viable microorganisms represented by Gram‐positive and Gram‐negative, aerobic, anaerobic, spore‐forming and asporogenous bacteria . In numerous permafrost deposits, primarily of lacustrine and marine origin, viable methane‐producing archaea have been found …”
Section: Diversity Of Organisms In Permafrostmentioning
confidence: 99%
“…Highly mineralized ancient aquatic ecosystems (cryopegs), which are characterized by subzero temperatures, were found in the Arctic at a depth of several tens of meters [1]. Microbiological study of these water brines within permafrost has shown that they are inhabited by cryophilic prokaryotes, including anaerobic bacteria of different physiological groups [1][2][3][4][5]. Nevertheless, information on the microbial diversity of cryopegs remains very scarce, and there are significant functional gaps in the trophic chains of the anaerobic part of the cycles of biogenic elements, including the sulfur cycle.…”
mentioning
confidence: 99%